The Impact of Rail Transport on Real Estate Prices: An Empirical Analysis of the Dutch Housing Market - Ghebreegziabiher Debrezion; Eric Pels; Piet Rietveld (Tinbergen Institute, 2006)
A hedonic pricing model is estimated to analyse the impact of railways on house prices in terms of distance to railway station, frequency of railway services and distance to the railway line. Correcting for a wide range of other determinants of house prices we find that dwellings very close to a station are on average about 25% more expensive than dwellings at a distance of 15 kilometres or more. A doubling of frequency leads to an increase of house values of about 2.5%, ranging from 3.5% for houses close to the station to 1.3% for houses far away. Finally we find a negative effect of distance to railways, probably due to noise effects. Two railway station references were used in the analysis: the nearest and most frequently chosen station in the post code area. This distinction indicates that railway station accessibility is a more complex concept than one might think. It involves competition between railway stations.
Keywords: R3; R4; 330; property value; railway station; accessibility; hedonic pricing method